2004
DOI: 10.1016/s0002-9440(10)63756-x
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Intestinal Structural Integrity by Zinc Is Independent of Metallothionein in Alcohol-Intoxicated Mice

Abstract: Intestinal-derived endotoxins are importantly involved in alcohol-induced liver injury. Disruption of intestinal barrier function and endotoxemia are common features associated with liver inflammation and injury due to acute ethanol exposure. Zinc has been shown to inhibit acute alcohol-induced liver injury. This study was designed to determine the inhibitory effect of zinc on alcohol-induced endotoxemia and whether the inhibition is mediated by metallothionein (MT) or is independent of MT. MT knockout (MT-KO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Zinc supplementation attenuated ethanol-induced increases in serum endotoxin levels, serum ALT activity, and hepatic TNF-α levels. These changes were associated with prevention of ethanol-induced liver injury (Lambert et al, 2003;Lambert et al, 2004). These results suggest that zinc brought these changes, at least in part, by preventing ethanol-induced transfer of endotoxin from intestine to circulation which could be ascribed to preservation of intestinal morphology and permeability.…”
Section: Preservation Of Intestinal Epithelial Barrier Functionmentioning
confidence: 72%
See 2 more Smart Citations
“…Zinc supplementation attenuated ethanol-induced increases in serum endotoxin levels, serum ALT activity, and hepatic TNF-α levels. These changes were associated with prevention of ethanol-induced liver injury (Lambert et al, 2003;Lambert et al, 2004). These results suggest that zinc brought these changes, at least in part, by preventing ethanol-induced transfer of endotoxin from intestine to circulation which could be ascribed to preservation of intestinal morphology and permeability.…”
Section: Preservation Of Intestinal Epithelial Barrier Functionmentioning
confidence: 72%
“…In rats, chronic ethanol ingestion significantly impaired zinc absorption in the ileum, which is the most active area of zinc uptake in the intestine (Antonson and Vanderhoof, 1983). Similarly in mice, acute alcohol treatment decreased zinc concentration in the ileum (Lambert et al, 2004). Using a mouse model of acute alcohol toxicity mimicking human binge drinking (Carson and Pruett, 1996), researchers investigated whether zinc supplementation could preserve intestinal permeability that is increased by alcohol consumption.…”
Section: Preservation Of Intestinal Epithelial Barrier Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc deficiency in Caco-2 cells not only induced membrane barrier damage but also increased neutrophil transmigration (16). Our previous study (29) showed that zinc protects against acute alcohol intoxication-induced intestinal histopathological changes independent of MT, suggesting the possibility that other zinc-binding proteins may mediate the effects of zinc. The present study demonstrated that zinc deprivation disassembles the tight-junction proteins, suggesting a novel mechanism of how zinc modulates the epithelial barrier.…”
Section: Discussionmentioning
confidence: 94%
“…It is conceivable that lack of MT in the MT Ϫ/Ϫ trans animals led to greater lipid peroxidation as a result of lower cellular zinc levels. MT deficiency may compromise tissue zinc status and limit zinc availability under conditions of stress, thus leading to increased tissue damage (26). Importantly, zinc has been shown to stabilize membrane integrity and inhibit lipid peroxidation (7,8).…”
Section: Discussionmentioning
confidence: 99%